Building a Better Union : Incentivizing Structural Reforms in the Euro Area - Banerji, Angana (IMF Working Papers; Working Paper, 2015)
The momentum for structural reforms is waning in the euro area at a time when even faster progress is needed to boost productivity and growth, achieve real economic convergence, and improve the resilience of the monetary union. What can the European Union (EU) institutions do to bridge this divide? This paper argues for greater simplicity, transparency and accountability in the EU governance framework for structural reforms. Our three interrelated proposals-'outcome-based' benchmarking; better use of existing EU processes to strengthen oversight and reduce discretion; and improved financial incentives-could help advance reforms. Ex post monitoring by an independent EU-level 'structural council' and ex ante policy innovation by national productivity councils could strengthen accountability and ownership. Deeper governance reforms should be considered in the medium-term with a view toward a greater EU role in promoting convergence.